Identifikasi Atribut Rasa dan Aroma Mayonnaise dengan Metode Quantitative Descriptive Analysis - Dwi Rahmawati; Nuri Andarwulan; Hanifah Nuryani Lioe (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Quantitative descriptive analysis (QDA) is a descriptive sensory technique commonly used to develop sensory description of a food product with some attributes and their references together with specific scores. Trained panelists were involved in the analysis. The QDA analysis consists of focus group discussion (FGD), panelists training, and sensorial evaluation. This study determined sensory attributes of mayonnaise and their references by QDA. Eleven sensorial attributes of mayonnaise were obtained by FGD. The aroma attributes were identified as lemon aroma, eggy aroma, mustard aroma, and oily aroma. The taste attributes were salty taste, umami taste, sweet taste, sour taste, eggy taste, mustard taste and oily taste. The result of sample evaluation by QDA showed that oily aroma and oily taste gave strong attributes on mayonnaise.